2016
DOI: 10.1088/1741-2560/13/2/025002
|View full text |Cite
|
Sign up to set email alerts
|

Temporal properties of network-mediated responses to repetitive stimuli are dependent upon retinal ganglion cell type

Abstract: Objective To provide artificially-elicited vision that is temporally dynamic, retinal prosthetic devices will need to repeatedly stimulate retinal neurons. However, given the diversity of physiological types of retinal ganglion cells (RGCs) as well as the heterogeneity of their responses to electric stimulation, temporal properties of RGC responses have not been adequately investigated. Here, we explored the cell type dependence of network-mediated RGC responses to repetitive electric stimulation at various st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
45
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 68 publications
9
45
0
Order By: Relevance
“…They found that visual ON cells tended to respond during the anodal phase of a slow (5 Hz) sine wave while OFF cells responded during the cathodal phase. Other recent contributions to growing evidence of cell-type selective stimulation include (Twyford & Fried 2016;Guo et al 2014;Im & Fried 2016;Goetz et al 2015;Im et al 2018;Guo et al 2018;Qin et al 2017).…”
Section: Type-specific Retinal Stimulationmentioning
confidence: 99%
“…They found that visual ON cells tended to respond during the anodal phase of a slow (5 Hz) sine wave while OFF cells responded during the cathodal phase. Other recent contributions to growing evidence of cell-type selective stimulation include (Twyford & Fried 2016;Guo et al 2014;Im & Fried 2016;Goetz et al 2015;Im et al 2018;Guo et al 2018;Qin et al 2017).…”
Section: Type-specific Retinal Stimulationmentioning
confidence: 99%
“…The clinical relevance of sinusoidal stimulation thus appears to be limited 25 . Varying stimulus parameters such as shape, repetition rate, duration and charge allowed to identify stimulus regimes that maximize the response ratio of ON and OFF RGCs [27][28][29][30][31] .…”
mentioning
confidence: 99%
“…The desensitization phenomenon has been observed experimentally in both direct and network mediated responses of RGCs. For network mediated responses, in the low frequency range (below 10 Hz), Im and Fried (2016) showed desensitization in OFF RGCs, but not in ON RGCs. However, Walston et al (2018) observed desensitizing responses in ON bipolar cells at frequencies greater than 6 Hz.…”
Section: Temporal Resolutionmentioning
confidence: 93%
“…Also, the stimuli that activated photoreceptors yielded better correlations than those activating bipolar cells. In a following study (Im and Fried, 2016), they examined the network-mediated responses to repetitive stimulation and also found differences between ON and OFF cells. In both brisk transient and brisk sustained ON cells, they showed a reset phenomenon, in which each new stimulus elicited a brief burst of spikes.…”
Section: Temporal Resolutionmentioning
confidence: 99%